THE RELATIONSHIP BETWEEN THE USE OF ROUTING AND SWITCHING E-MODULES AND STUDENT LEARNING MOTIVATION - Mai Saro; Detri Amelia Chandra (RADJA PUBLIKA, 2025)
This study aims to examine the relationship between the use of e-modules and student learning motivation in the Routing and Switching course in the Informatics Engineering Study Program at Rokania University. The background of this study is the low learning motivation of students due to the dominance of conventional learning methods. The method used is a quantitative approach with data collection techniques through questionnaires distributed before and after the use of e-modules. The instrument was tested for validity and reliability, which showed that all items were valid and had high consistency, with a Cronbach's Alpha value of 0.853. The results of the linearity test showed that the relationship between the two variables was linear, with an F count of 7.443 and a significance of <0.001. The Pearson correlation test showed a coefficient of 0.790, which means there is a strong and positive relationship between the use of e-modules and student learning motivation. These findings indicate that e-modules are able to increase learning motivation through flexible, interactive, and easily accessible presentation of materials. Therefore, e-modules can be used as an effective alternative learning media in increasing student participation and enthusiasm for learning in the digital era.